Thyroidectomy Surgical Technique Minimizing Aggression to Recurrent Nerve - Tchekmedyian, Vartan; Aguirre, Carlos; Ricciardi, Norma; Geninazzi, Héctor; Delbene, Roberto; Praderi, Luis (Cirugía del Uruguay, 1981)
The authors propase a technique for thyroidectomy which is not intended to be original. It is aimed fundamentally at maintaining anatomic and functional indemnity to recurrent nerve.